HIV treatment and worker absenteeism: quasi-experimental evidence from a large-scale health program in South Africa - Jockers, Dominik; Langlotz, Sarah; French, Declan; Bärnighausen, Till (Journal of health economics, 2021)
Over the past decade, large-scale HIV antiretroviral therapy (ART) programs have proven hugely successful in improving the life expectancy of people living with HIV. However, the extent to which treatment allows patients to maintain a productive work life remains an open question. We applied an instrumental variable method based on individual CD4 counts and exogenously changing treatment guidelines to identify the causal effect of ART on health-related absenteeism rates among workers living with HIV. We used monthly data from the occupational health program of one of the world's largest mining companies in South Africa (128,052 observations among 1,924 workers, from 2009 to 2017). Eighteen months after ART initiation, the treatment significantly reduced absenteeism by 1.033 days per worker and month. Using publicly available wage and treatment cost data, we find that the cost savings due to the absenteeism effect of ART alone outweigh treatment costs in the mining sector in several sub-Saharan African countries.
Gesehen am 05.11.2021